Respuesta :

Factored Form:
x^2 - 4x - 5
Simplifying:
x^2 +  - 4x +  - 5 = 0

Reorder the terms:
- 5 +  - 4x + x^2 = 0

Solving for variable " x":
Subproblem 1:
Set the factor ( - 1 +  - 1x) equal to Zero and attempt to solve.

Simplifying:
- 1 +  - 1x = 0

Solving:
- 1 +  - 1x = 0
Move all terms containing x to the left, all other terms to the right

Add 1 to each side of equation:
- 1 + 1 +  - 1x = 0 + 1

Combine Like Terms: 0 + 1 = 1
x =  - 1


Divide each side by - 1
x =  - 1

Simplifying:  x =  -  1


Subproblem 2: Set the factor (5 +  -  1x) equal to Zero attempt to solve

Simplifying:
5 +  - 1x = 0

Move all terms containing x to the left, all other terms to the right
Add - 5 to each side of the equation
5 +  - 5  +  - 1x = 0 + 5

Combine Like terms:  5 +  - 5 = 0
0 +  - 1x = 0 +  - 5
- 1x = 0 +  - 5

Combine Like Terms: 0 +  - 5 = - 5
- 1x =  - 5

Divide each side by - 1
x = 5

Simplifying:
x = 5

Solution:
x = { - 1,  5}





Answer when factored:
(x + 1)(x - 5)







hope that helps!!!

Answer:

D

Step-by-step explanation:

ACCESS MORE